1990
DOI: 10.1007/bf02398889
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic morphology of recurrent stenoses after percutaneous transluminal coronary angioplasty: are lesions longer at restenosis?

Abstract: Angiographic morphology was analysed in 32 patients who developed restenosis after initially successful coronary angioplasty. The mean minimal luminal diameter of the dilated coronary segments increased from 0.9 mm to 2.3 mm after dilatation, but decreased to 0.9 mm at restenosis. The reference diameter was unchanged after dilatation and at restenosis. Mean stenosis length before the initial angioplasty was 7.0 mm but at the repeat procedure had increased to 8.7 mm (mean increase 1.7 mm, 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…(80,83,845). A number of factors have been associated with the propensity to develop stent restenosis, including small vessel size (846), smaller postprocedure minimum lumen diameter (847), higher residual percent diameter stenosis (848), lesions located in the LAD (83), stent length, and the presence of diabetes mellitus (721,841,842,844,(846)(847)(848). Stent restenosis may occur within the stent, due to intimal hyperplasia, or at the stent margins, due to both intimal hyperplasia and arterial remodeling (849).…”
Section: Management Strategies For Restenosismentioning
confidence: 99%
“…(80,83,845). A number of factors have been associated with the propensity to develop stent restenosis, including small vessel size (846), smaller postprocedure minimum lumen diameter (847), higher residual percent diameter stenosis (848), lesions located in the LAD (83), stent length, and the presence of diabetes mellitus (721,841,842,844,(846)(847)(848). Stent restenosis may occur within the stent, due to intimal hyperplasia, or at the stent margins, due to both intimal hyperplasia and arterial remodeling (849).…”
Section: Management Strategies For Restenosismentioning
confidence: 99%
“…Some studies have suggested that lesions become longer and more severe after repeat PTCA of restenotic lesions (840,841). In a serial angiographic study, the mean stenosis length before the initial angioplasty was 7.0 mm but increased to 8.7 mm at the time of the repeat procedure (an increase of more than 1.7 mm, 95% CI 0.6 to 2.8 mm, P less than 0.01) (841).…”
Section: Clinical and Angiographic Factors For Restenosis After Ptcamentioning
confidence: 95%
“…In a serial angiographic study, the mean stenosis length before the initial angioplasty was 7.0 mm but increased to 8.7 mm at the time of the repeat procedure (an increase of more than 1.7 mm, 95% CI 0.6 to 2.8 mm, P less than 0.01) (841). A history of restenosis may also predict the risk for subsequent restenosis after PTCA of a new lesion (104).…”
Section: Clinical and Angiographic Factors For Restenosis After Ptcamentioning
confidence: 97%
See 1 more Smart Citation